2019
DOI: 10.1088/1674-1056/ab53cc
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement teleportation via a couple of quantum channels in Ising–Heisenberg spin chain model of a heterotrimetallic Fe–Mn–Cu coordination polymer*

Abstract: We investigate the teleportation of an entangled state via a couple of quantum channels, which are composed of a spin-1/2 Heisenberg dimer in two infinite Ising–Heisenberg chains. The heterotrimetallic coordination polymer CuIIMnII(L1)][FeIII(bpb)(CN)2]·ClO4 · H2O (abbreviated as Fe–Mn–Cu) can be regarded as an actual material for this chain. We apply the transfer-matrix approach to obtain the density operator for the Heisenberg dimer and use the standard teleportation protocol to derive the analytical express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…11(a), we fixed J 0 = 1, J = 4 and ∆ = 0.5. As can be seen, the average fidelity remains above 2/3 for weak magnetic fields in the original model [47]. When the impurity is induced in the model, in contrast to the original case, the behavior of the average fidelity becomes more robust, enabling teleportation of information in the regions of very strong magnetic fields.…”
Section: A Average Fidelity Of Teleportationmentioning
confidence: 90%
See 2 more Smart Citations
“…11(a), we fixed J 0 = 1, J = 4 and ∆ = 0.5. As can be seen, the average fidelity remains above 2/3 for weak magnetic fields in the original model [47]. When the impurity is induced in the model, in contrast to the original case, the behavior of the average fidelity becomes more robust, enabling teleportation of information in the regions of very strong magnetic fields.…”
Section: A Average Fidelity Of Teleportationmentioning
confidence: 90%
“…In panels of this figure, solid lines describe the average fidelity of the original model recently investigated by Y. -D. Zheng et al [47]. In Fig.…”
Section: A Average Fidelity Of Teleportationmentioning
confidence: 91%
See 1 more Smart Citation
“…At fixed values of the model parameters, the specific value of the negativity (27) pertinent to the nondegenerate quantum ferrimagnetic ground state |QFI + is surprisingly much greater at nonzero magnetic fields than the zero-field value (24) inherent to the two-fold degenerate quantum ferrimagnetic phase |QFI ± forming the respective ground state in the zero-field limit. It could be thus concluded that the Zeeman splitting of energy levels due to the external magnetic field leads to an unexpected sudden rise of the bipartite quantum entanglement of the mixed spin-(1/2,1) Heisenberg dimer, which is in contrast with naive expectation that the magnetic field suppresses the quantum entanglement.…”
Section: A Quantum Entanglementmentioning
confidence: 95%
“…It is noteworthy that entanglement measures such as negativity [13][14][15] or concurrence [16] can be related via certain witnesses to thermodynamic quantities [17,18], which additionally offer an intriguing possibility for experimental testing [19,20]. Some quantum protocols such as a quantum teleportation of information cannot be even realized without many-particle entangled states [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%